2018
DOI: 10.2141/jpsa.0170083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acids on Growth Performance, Carcass Characteristics, Meat Quality, and Carnosine Concentration in Broiler Chickens

Abstract: The aim of this research was to investigate the deposition of carnosine in broiler muscles by feeding treatments comprising β-alanine, L-histidine, and magnesium oxide in various concentrations. The research was carried out on 120 Cobb 500 broilers divided into four groups. From weeks four to six, broilers were fed finisher mixtures as follows: P1, control group; P2, 0.5% β-alanine + 0.24% MgO; P3, 0.25% L-histidine + 0.24% MgO; and P4, 0.20% β-alanine + 0.10% L-histidine + 0.24% MgO. This paper presents the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 43 publications
4
26
2
Order By: Relevance
“…Supplementation of His reportedly increases the Car concentrations in breast muscle tissue ( Kai et al., 2015 ; Kralik et al., 2015 ). However, Kralik et al. (2018) described an increase in Car concentration in breast muscle tissue by feeding a combination of βA and His, but not with the stand-alone supplementations, thus deviating from the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Supplementation of His reportedly increases the Car concentrations in breast muscle tissue ( Kai et al., 2015 ; Kralik et al., 2015 ). However, Kralik et al. (2018) described an increase in Car concentration in breast muscle tissue by feeding a combination of βA and His, but not with the stand-alone supplementations, thus deviating from the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…According to other studies, βA could increase the concentration of HCD in muscle tissue ( Tomonaga et al., 2012 ; Kralik et al., 2015 ; Qi et al., 2018 ). This was not observed in our study, as well as in the study of Kralik et al. (2018) .…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Carnosine is a naturally occurring skeletal muscle dipeptide comprised of β-alanine and histidine ( Crush, 1970 ), and it reduces oxidative stress by its peroxyl radical-trapping ability ( Kohen et al., 1988 ). An increase in carnosine in broiler meat improves its drip loss ( Kralik et al., 2018 ), 2-thiobarbituric acid reactive substances values ( Hu et al., 2009 , Kralik et al., 2018 ), and shear force value ( Hu et al., 2009 ). Ascorbic acid is also an antioxidant that partly improves growth performance and meat quality, such as pH and color in broilers under heat stress ( Imik et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the blood TAS level at slaughter age in the T3 group was higher than that of the poultry in T1 group, this may have been caused by the increase in the concentration of carnosine, which has strong antioxidant ability (O'Neill et al, 1998;Cong et al, 2017;Kralik et al, 2018;Qi et al, 2018;Kopec et al, 2020;Shimamoto et al, 2020). These studies reported that the antioxidant capacity of the PM increased with the βA supplement (Qi et al, 2018).…”
Section: Resultsmentioning
confidence: 94%